DISTRIBUTION OF MICROPLASTICS IN COASTAL SURFACE WATERS AT BROOKE’S POINT, PALAWAN, PHILIPPINES - H. Jeffrey de Castro (Tạp chí Khoa học Đại học Đà Lạt, 2024)
Coastal surface water samples obtained from 11 sites at Brooke’s Point, Palawan, were subjected to sieving and visual analysis of microplastics. Microplastics were detected in all samples, with blue fiber-shaped particles being the most abundant. Variations in the mean concentration of microplastics across sample sites were investigated for trends in microplastic distribution. Geographical features, wind patterns, rivers, and the direction of ocean waves were suspected to influence the transport of microplastics. The results provide a call to local governing bodies to formulate policies that address the issue of microplastic contamination and increase environmental awareness among the local population.